The Impact of Green Finance, Agriculture Growth and Creativity on Carbon Emissions of High Carbon Emissions Producing Countries - Kapa, Maximillian M. J.; Nalle, Agus A.; Tamelan, Paul G.; Wisetsri, Worakamol (International Journal of Energy Economics and Policy, 2022)
Correct predictions are needed to measure the future level of energy performance across the country in sequence to develop clear policies for monitoring and reducing carbon and other harmful emissions. Using the most correct and recognized procedures of the six countries like China, Japan, India, Indonesia, Russia, and the United States that account for 61% of global emissions, we have made a correct guess on the number of carbon emissions. Thus, the present study investigates the impact of green finance, agriculture economics and creativity on carbon emission. The data was extracted from WDI covering the period from 2006 to 2020. The paper employed Fixed effect model as well as robust standard error to test the hypotheses. The results revealed that green finance, agriculture economics and creativity share negative relation with the carbon emission of selected countries, while other variables such as population and economic growth shares a positive connection with carbon emission. This research also proposes some enlightenment for researchers and policymakers who admire and decrease carbon emissions.